EFFECTIVENESS OF E-FORMATIVE ASSESSMENT TO ENHANCE CONCEPTUAL UNDERSTANDING IN STATIC FLUID - Zahrotul Ula Irma (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2022)
This study aims to test the effectiveness of e-formative assessment to enhancing students' conceptual understanding on static fluid. The research with the one group pretest-posttest design method involved 30 students. The pretest and posttest instruments consisted of 10 multiple choice questions accompanied by reasons with a reliability of 0.629 and a cognitive level of C3-C5. The formative test instrument provided consists of 10 multiple choice questions with indicators and difficulty levels equivalent to the pretest and posttest. The results of the Wilcoxon test showed that the average posttest score was significantly higher than the pretest average score (p=.000). The effect size value of 0.88 indicates that the e-formative assessment has a moderate effect on students' conceptual undersatnding of static fluid material. One of the determinants of e-formative assessment can enhance students' conceptual understanding is the provision of feedback. Through feedback, misconceptions experienced by students can be immediately corrected. E-formative assessment provided via web is also more effective in providing fast and precise feedback to all students with a variety of responses.